Techno-economic environmental assessment of advanced intercooled propulsion systems - Najafi Saatlou, Esmail (Cranfield University, 2012)
A tool based on a Techno-economic and Environmental Risk Assessment (TERA) framework is useful at the preliminary stage of an aero engine design process, to conceive and assess engines with minimum environmental impact and lowest cost of ownership, in a variety of emission legislation and taxation policy scenarios. This research was performed as part of the EU FP6 New Aero engine Core concepts (NEWAC) programme which was established to assess the potential of innovative gas turbine core technologies to enhance thermal efficiency thereby reducing CO2 emissions and fuel consumption. A representative prediction of engine life and mission fuel burn at the earliest possible design stage is a crucial task that can provide an indication of the approximate overall engine direct operating costs. Two aero engines, a conventional turbofan and a conceptual intercooled turbofan, were assessed and optimised using the TERA approach to identify the designs that provided the maximum time between overhaul (and therefore the minimum maintenance costs). In order to perform these assessments (which included sensitivity and parametric analyses, and optimisation studies) several models were developed and integrated in an optimisation framework. A substantial effort was devoted to the development of a detailed lifing model that calculates the engine life with a reasonable level of accuracy by integrating physics based oxidation, creep and fatigue models. The results obtained from the study demonstrate that an engine optimised for maximum time between overhaul requires a lower overall pressure ratio and specific thrust but this comes at the cost of lower thermal efficiency and therefore higher mission fuel burn. The main contribution to knowledge of this work is a multidisciplinary TERA assessment of a novel intercooled conceptual aero engine. Particular emphasis is placed on the design space exploration and optimisation studies to identify the designs that may offer the largest time between overhaul. The consequent implications therefore this may have on mission fuel burn and direct operating costs. In addition to refining the various TERA models, one of the main recommendations for further work is to optimise the engines for minimum direct operating cost to identify the best economic compromise between engine life and mission fuel burn. This can be done by considering different fuel prices and under a variety of hypothetical emission taxation scenarios, to identify the circumstances in which intercooled engine technology may become economically viable.